2012
DOI: 10.1086/661508
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Good Teachers: Patterns of Teacher Quality in Two Mexican States

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…For example, Falus and Goldberg (2011) found that a larger proportion of teachers in schools located in high and middle class neighborhoods have a higher education training, know how to operate a computer and are more experienced than in schools located in low income neighborhoods and in rural schools. This pattern is found in all countries and is confirmed in studies of countries as diverse as Mexico and Uruguay (Luschei, 2012;Luschei & Carnoy, 2010).…”
Section: Background and Framework For The Study Teacher Policies In Lsupporting
confidence: 70%
“…For example, Falus and Goldberg (2011) found that a larger proportion of teachers in schools located in high and middle class neighborhoods have a higher education training, know how to operate a computer and are more experienced than in schools located in low income neighborhoods and in rural schools. This pattern is found in all countries and is confirmed in studies of countries as diverse as Mexico and Uruguay (Luschei, 2012;Luschei & Carnoy, 2010).…”
Section: Background and Framework For The Study Teacher Policies In Lsupporting
confidence: 70%
“…As noted elsewhere (Santibañez et al 2005; Luschei 2012), schooling infrastructure and quality have not necessarily kept pace with rising educational aspirations in many parts of rural Mexico, and employment opportunities that reward education also remain scarce in these communities. The need to migrate domestically for education was a recurrent perception expressed by both boys and girls, providing a partial explanation for the increasing salience of ‘schooling migration’ illustrated in Table 2.…”
Section: Resultsmentioning
confidence: 95%
“…Extant research largely views migration and schooling as competing outcomes for Mexican youth (Kandel and Massey 2002; Meza and Pederzini 2009; McKenzie and Rapoport 2011). Yet, because educational infrastructure and quality have not kept pace with schooling demand in many impoverished parts of the country, domestic migration for schooling is an increasingly salient decision for rural youth (Santibañez et al 2005; Luschei 2012). Moreover, a family’s ability to send children to Mexican cities for schooling rises with remittances received from migrants abroad and/or with logistical and financial support from migrants within Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…Occupations tend to be prestigious if they involve highly complex work and thus require a high level of education or a license (Ingersoll and Merill 2011; Rowan 1994). Literature suggests that credentials are important indicators of the degree of professionalization (Ingersoll and Merill 2011) as well as of teacher quality (Akiba et al 2007; Darling-Hammond 2000; Luschei 2012). Many countries such as the United States have made efforts to raise certification standards (Constantine et al 2009; Darling-Hammond and Sykes 2003) in order to strengthen professionalization of teaching as well as to improve teachers’ quality.…”
Section: The Current Study: Roles Of National Contextsmentioning
confidence: 99%